Early SARS‐CoV‐2‐associated acute transverse myelitis: A case for neurotropism?. (13th July 2022) - Lu, Irene F.; Cornish, Jack S.; Ashok, Aadith; Chen, Siew Kar; Athan, Eugene; Hughes, Andrew
Abstract: There are increasing reports of immune‐mediated and para‐infectious syndromes beyond the well‐known respiratory manifestations of severe‐acute‐respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. However, the spectrum of severe neurological sequelae of SARS‐CoV‐2 remains undefined. We present the case of a 66‐year‐old female with rapidly progressive lower limb neurology 3 days post SARS‐CoV‐2 infection. Clinical and radiological findings were in keeping with transverse myelitis and treatment success was achieved with methylprednisolone and remdesivir. This report will discuss the associations between SARS‐CoV‐2 and acute transverse myelitis. We believe this is one of few described cases of early SARS‐CoV‐2‐associated transverse myelitis secondary to neurotropism and the first successfully treated with the inclusion of remdesivir in the therapeutic regimen.